Um breve panorama da Educação de Jovens e Adultos: um olhar sobre a realidade do município de Mauá - Martins, Izaura Naomi Yoshioka (2014)
The modality of education involved on young and adult education (EJA) program demands reflections, mainly on historical aspect, that bounce its importance as historic social debt to people excluded of the right to study. Several authors contribute to a reflection on this theme, attending to the specificity of the work with learners, due to the fact that it isn t a question of compensation work, or substitution, but a recovery of their humanity, a work of awareness, of lifetime education. With the LDB 9394/96 and the politics of treatment methods, some actions get triggered, but with results that still do not solve the demand, be this on number or on financial and formative investments. Although the principles are in official documents and curricula, they are theories that need study and reflection to becoming actions, due to the fact that the public administration and the teachers still act through regular education methods. The objective of this work is to make an analysis of the treatment of this modality of education in the city of Mauá, located in the metropolitan region of the state of São Paulo. By the analysis of this city, its population, demands and forms of treatment of this modality, and from official documents, statistic data, interviews with learners, we will reflect about the EJA that the city of Mauá has and the EJA that the city of Mauá needs